Pengembangan Aplikasi Sensor Giant Magnetoresistance seri AB001-02 untuk Desain Alat Ukur Massa berbasis Mikrokontroler ATMega328p - Fanny Maulida; Ahmad Aminudin; Waslaluddin (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2025)
In this research, the application of Giant Magnetoresistance sensor AB001-02 series for mass measurement using ATMega328p microcontroller has been developed. Characterization is done by bringing a neodymium magnet closer to the GMR sensor. From the tests conducted, it is known that the farthest range detected is 3.5 cm with the optimal sensitivity area in the range of 0 - 1.5 cm. Based on the tests that have been carried out, changes in mass result in spring displacement (∆x). Displacement causes changes in the magnetic field read by the GMR sensor so that the output voltage of the GMR sensor changes. The greater the mass given, the greater the output voltage of the GMR sensor. The results show the sensitivity of the GMR sensor on mass measurement is 0.0816 Volt/Kg and has a measurement range of 0 - 4.3 Kg with a resolution of 100 g.